Sustainable Tourism Development Through Improving the Role of Customary Village - Purnamawati, I Gusti Ayu (International Journal of Social Science and Business, 2021)
This study aims to analyze the potential of the Customary Village in tourism development, its position, and function in Bali Province. This research is a socio-legal study with a legal and case approach, legal analysis techniques in the form of legal hermeneutics and is analyzed through the theory of legal pluralism, and the concept of recognition of the Customary Law Community. This research was conducted in the area of Bali Province based on local wisdom with the concepts of Parahyangan, Pawongan, and Palemahan. The system and implementation of customary law, institutional Sabha Customary Village and Kerta Customary Village, custom advisory institutions, religion, traditions, arts, and culture, as well as local wisdom of indigenous peoples. Pasraman as an educational institution based on Hinduism for the development of identity, moral integrity, and quality of Balinese society, traditional village security institutions, and traditional village economic institutions by the principles and objectives of tourism, namely the welfare of the community. Especially the Krama Customary Village. The results showed that the Balinese Customary Village in tourism development is an autonomous Balinese customary institution, traditional cultural communities, indigenous peoples, and the collective identity of the people in Bali based on customary law to achieve common goals based on the Tri Hita Karana.